(untitled) (Research, Society and Development, 2021)
There are several impacts to the environment caused by meal production processes. The research was carried out with the objective of evaluating food waste associated with acceptance and satisfaction of the hospital diet of inpatients at the University Hospital in Campina Grande-PB. This is a quantitative cross-sectional study, where the weighing system was applied before and after the meal and subsequently a questionnaire was applied regarding the satisfaction of the diets offered to the interns. We highlight the option of very satisfied for the attributes: flavor 33.98%; appearance 33%; color 35.92%; texture 33.98%; temperature 46.60%; distribution method 51.45%; container served 53.39% and quantity served 41.74%. Although the study shows good satisfaction in the offered diet, there is still a waste with a value of 30%, which exceeds the acceptable limit of 20% for the sick community, demonstrating a reduced consumption of energy and protein intake by the patient, causing a double increase in the risk of death during a hospital stay. Regarding both genders, we found that the male gender had a lower waste (27.88%) compared to the female gender (32.79%). Corroborate the importance of educational actions in order to mitigate these food waste and avoid malnutrition in patients, hospital costs and impacts on the environment, conducting a patient satisfaction survey every three months; display on murals the amount of daily food waste; and donating surplus food to people at food and nutritional risk, supported by Law 14016 of 23 June 2020.